(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Santyana’s writings call repeated attention to the ultimate significance which form possesses for experience in giving meaning and value to our activities. Unless a man is interested in the characters which things have or might have, he can hardly be said to live at all, in any morally significant sense. One strain of Santyana’sthought, consists of a combination of materialism in metaphysics, humanism in morals, and realistic methodology in the theory of knowledge. These doctrine receive dominate expression in the works of the middle period, especially in his book (The life of Reason). In this essay we will try to illustrate Santyana’s materialism tendency, especially in the book (The life of Reason), and we will try to prove that his materialism was not of the myopic sort which believes that the material existence were the sole reality